Persistent fetal circulation - D’cunha, Chrysal (Pulsus Group Inc, 2001)
Persistent fetal circulation (PFC), also known as persistent pulmonary hypertension of the newborn, is defined as postnatal persistence of right-to-left ductal or atrial shunting, or both in the presence of elevated right ventricular pressure. It is a relatively rare condition that is usually seen in newborns with respiratory distress syndrome, overwhelming sepsis, meconium and other aspiration syndromes, intrauterine hypoxia and ischemia, and/or neonatal hypoxia and ischemia. This condition causes severe hypoxemia, and, as a result, has significant morbidity and mortality. Improved antenatal and neonatal care; the use of surfactant; continuous monitoring of oxygenation, blood pressure and other vital functions; and early recognition and intervention have made this condition even more rare. In modern neonatal intensive care units, anticipation and early treatment of PFC and its complications in sick newborns are commonplace. Thus, severe forms of PFC are only seen on isolated occasions. Consequently, it is even more imperative to revisit PFC compared with the time when there were occasional cases of PFC seen in neonatal intensive care units, and to discuss evolving treatment and management issues that pertain to this syndrome.